Three-Dimensional Evaluation of the Effects of Kinesio Taping on Postoperative Swelling and Pain after Surgically Assisted Rapid Palatal Expansion - Murat Ulu; Özgür Gözlüklü; Çiğdem Kaya; Nuri Ünal; Hüseyin Akçay (Stilus Optimus, 2018)
Objectives: The purpose of the present study was to evaluate the effects of kinesio taping on pain and swelling after surgically assisted rapid palatal expansion. Material and Methods: A total of 21 (12 male and 9 female) patients with transverse maxillary deficiency were enrolled in the study. Kinesio taping (KT) was applied unilaterally in each patient, whereby sides of the face with KT application were included into the (a) KT group and the other sides were included into the (b) non-KT group. Changes in facial volume were evaluated on digital images using the 3dMD Face System. Pain scores were assessed at postoperative days 1, 2, 3, 4, 5, 6, and 7 using the visual analog scale (VAS). Two-way repeated measures analysis of variance and Mann Whitney U test were used for statistical analyses. Results: Swelling was significantly lower in the KT group compared to the non-KT group from T0 to T1 (36.42 [SD 19.71] mm3 vs. 183.84 [SD 49.33] mm3) and was significantly greater in the non-KT group compared to the KT group from T0 to T2 (70.88 [SD 15.73] mm3 vs. 21.46 [SD 13.39] mm3) (P < 0.001 for both). The VAS scores were significantly lower in the KT group compared to the non-KT group at all time points (P < 0.05). Conclusions: The application of kinesio taping after maxillofacial surgery reduced the pain and swelling in the postoperative period. Kinesio taping can be used as an alternative to other methods that are used for the reduction of postoperative complaints.